O uso do pool de plasma caseiro interfere no valor da rni? - Da Silva, Paulo Henrique (2012)
Introduction: The prothrombin time (PT) test is commonly used to monitor anticoagulant levels in patients undergoing oral anticoagulant therapy. Currently, anticoagulation levels have been assessed through the international normalized ratio (INR) value. Objective: The objective of this study was to determine if inhouse preparations of polled plasma, containing five (P5) and 20 (P20) samples, respectively, may be used as normal control of PT and to assess its interference in INR values. Material and methods: The experiment was performed in 32 days. Both polled plasma preparations were analyzed in comparison with a commercial control (PC). PT was performed for PC, P5 and P20 daily and the INR value for PC, P5 and P20 was assessed in patients undergoing oral anticoagulant therapy. The applied statistical tools were mean value (X), analysis of variance and Tukey test. Results: There were no statiscally significant differences in PT and INR for PC, P5 and P20. Conclusion: In-house polled plasma (P5 and P20) may be applied as normal control of PT and it does not interfere in the INR value.